Avances en la evaluación de la calidad de vida en el cáncer de pulmón: el sistema de medida de la eortc - Martínez, Enrique; Arraras, Juan Ignacio; Martínez, Maite (Psicooncología, 2006)
The aim of the present work is to present the situation of Quality of Life assessment in lung cancer. Quality of Life evaluation is quite useful in clinical practice and in clinical trials with this disease. Nowdays, there is a debate on the treatment of lung cancer in which Quality of Life assessment has a key role. The EORTC evaluation system and two other instruments for lung cancer are presented. Attention is given to important aspects related to Quality of Life assessment in this disease, like its prognostic function. A review of the present situation of the treatment for non small cell lung cancer in advanced disease, and of the key role of Quality of Life assessment in the progress of this treatment is presented.